FAKTOR YANG MEMPENGARUHI FIRM VALUE PADA PERUSAHAAN MANUFAKTUR TAHUN 2017-2019 - Kessya Kessya; Lukman Surjadi (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this research is to prove empirically the profitability, leverage, liquidity, growth opportunity of firm value. This study uses secondary data. The object in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. This research was conducted with a sample of 225 manufacturing company data. The data collection technique used in this study was purposive sampling processed using the E-Views ver 10.0 program. The results of this study indicate that all independent variables simultaneously (F test) can predict cash holding. The t test results show that liquidity (CR) has a significant positive effect on firm value, while profitability (ROA), leverage (DER), and growth opportunity (TAGR) have no effect on firm value.